Diagnostic Evaluation of Haematological Diseases Based on Bone Marrow Examination (Journal of Enam Medical College, 2023)
Background: Bone marrow examination is a safe invasive procedure and can provide sufficient explanation for unexplained cytopenias, leukaemia and other haematological disorders including metastases to the marrow by detailed morphological description of the marrow elements.Objective: To see the importance of bone marrow examination for the diagnosis of haematological disorders.Materials and Methods: It was a descriptive cross-sectional study comprising 196 patients who underwent bone marrow examination for evaluation of haematological disorders in the Department of Haematology, Enam Medical College and Hospital during the period of July 2012 to December 2019.Results: Total number of cases were 196, male to female ratio was 1.56:1 and majority of the patients were >18 years of age (84.69%). Common indications for bone marrow examination were pancytopenia (33.67%) and diagnosis of leukaemia/ myeloproliferative neoplasm (23.98%). In our study, haematological conditions were 79.08%. Among these malignant conditions were 55.10% and nonmalignant conditions were 23.98%. Aplastic anaemia (14.29%) and immune thrombocytopenia (7.65%) were the most common nonmalignant disorders. Common malignant disorders were acute myelogenous leukaemia (20.41%) and multiple myeloma (9.69%).Conclusion: Bone marrow examination is a simple and effective procedure in reaching the final diagnosis of haematological diseases.J Enam Med Col 2021; 11(1): 34-38